Epidemic analysis of patients positives HIV assisted at public hospital of reference in João Pessoa - PB - Sousa, Ana Carla A.; Duarte, Lívia R.; Costa, Stenio M.L. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: to approach the aids epidemic through the epidemiologist analysis of its clinical and socio-demographic variables is one of the strategies of control epidemic. Objective: to analyze the clinical profile epidemiologist from patients affected for aids in the city of João Pessoa, Paraiba. Methods: it’s treated of a descriptive epidemiologist research of secondary source of data. The population was formed by patients with HIV/aids attended in the Complexo Hospitalar Clementino Fraga (CHCF), during the year of 2007. The data had been gotten from the National Reporting Information System (SINAN) available by Epidemiology Sector of the CHCF. The investigated variables were: sexes, age group, educational level; category of exhibition and evolution’s case. The data were analysed through the evaluation from difference of percentages. Results: of the total from evaluated cases 63,12% was men; the majority, in both sexes, was heterosexuals (70,625%); the age group between 30 and 35 years (31,87%) predominated in the sample; most of the patients (35%) studied of the 1st one to 4th incomplete serie of the basic teaching (BT); 93,75% of the patients was derived of the urbane zone; 19,38% of the population died in the same year of the disease’s diagnosis. Conclusion: the investigated population was, in his majority formed by men, young adults; the majority heterosexual comes to corroborate with the heterosexual process of the epidemic; the predominance of patients with low educational level is one the signs of the aids’s poverty. The actions of the epidemic’s control must be that it intensifies between men, young persons and heterosexuals.